Effects of seed furrow liquid spraying device on sowing quality and seedling growth of maize - Wang, Wenjun; Wang, Wanpeng; Jia, Honglei; Zhuang, Jian; Wang, Qi (International Journal of Agricultural and Biological Engineering, 2019)
The two cultivation patterns, no-tillage and ridge cultivation, are widely used in maize planting in Northeast China. However, the seed bounce in the falling process and drought seriously at the seedling stage often occur to affect the sowing quality, mean emergence time, percentage of emergence, root biomass, aboveground biomass and root shoot ratio of maize, and eventually reduces the grain yield. To solve the problems, a seed furrow liquid spraying device was designed and thereby the effects of spraying water volumes [0 L/m (V0), 0.6 L/m (V1), 1.2 L/m (V2) and 1.8 L/m (V3)] and nozzle types [conical nozzle (N1) and sectorial nozzle (N2)] on the sowing quality and seedling growth of maize were studied. The water volume and nozzle type had significant effects on the sowing quality (QR, CV, LD), not seedling growth (MET, PE, RB, AB, RSR) (p<0.05). Spraying water into seed furrow further humidified the soils around the maize seeds, effectively suppressing the bounce and rolling of seed and significantly promoting the growth and development of seeds. The sowing quality in the N2 treatment was significantly better than that in the N1 treatment. The qualified rate of seed spacing was increased with the increase of the water volume (V3 > V2 > V1 > V0). However, the variability coefficient of seed spacing and lateral deviation of seed position were the opposite. The larger spraying water volume led to shorter mean emergence time (V0 > V1 > V2 > V3) and higher percentage of emergence (V3 > V2 > V1 > V0). The root biomass and aboveground biomass increased significantly with the enlargement of spraying water volume. Under different water volumes, the root shoot ratio differed significantly. The plants in the V1, V2 and V3 treatments had lower root shoot ratios compared with the V0 treatment. The increase of spraying water volume significantly reduced the root shoot ratio. The seed furrow liquid spraying device provides a reference for improving sowing quality and promoting seedling growth. Keywords: seed bounce, drought, spraying water volume, nozzle type, seed spacing uniformity, root shoot ratio DOI: 10.25165/j.ijabe.20191202.3799 Citation: Wang W J, Wang W P, Jia H L, Zhuang J, Wang Q. Effects of seed furrow liquid spraying device on sowing quality and seedling growth of maize. Int J Agric & Biol Eng, 2019; 12(2): 68–74.